2009
DOI: 10.1002/pip.903
|View full text |Cite
|
Sign up to set email alerts
|

Analytical model of solar thermophotovoltaic systems with cylindrical symmetry: Ray tracing approach

Abstract: An analytical model for a full solar thermophotovoltaic (STPV) system with cylindrical symmetry is presented. In contrast to the already published TPV models, this model considers both TPV optical cavity and absorber (or heating) systems. An analytical ray-tracing method has been used to analyse the radiation interchange within a TPV optical cavity. It allows us to calculate the portion of the absorbed power in each component within the system. Using this model, a broad analysis of an STPV system has been carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In our previous works concerning the theoretical analysis of STPV systems, we demonstrated that efficiencies and electrical power densities of about 10% and 3 W/cm could be achieved in the short term, using presently available devices [5]. Besides, efficiencies and electrical power densities above 30% and 50 W/cm , respectively, are plausible in the long term [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous works concerning the theoretical analysis of STPV systems, we demonstrated that efficiencies and electrical power densities of about 10% and 3 W/cm could be achieved in the short term, using presently available devices [5]. Besides, efficiencies and electrical power densities above 30% and 50 W/cm , respectively, are plausible in the long term [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we use the theoretical models presented in [5,46] to predict the performance of cylindrical STPV systems with improved photon recycling system. This analysis assumes that both the emitter and the cells are isothermal 7 Looking at Table I, we see that in this module the substrate has no groves to host the back-side copper tape, and consequently, the cells are not in good thermal contact with the substrate.…”
Section: Future Efficiency Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is because the relationship between these components is very complex and the efficiency of each component depends on all of them. They (Datas & Algora, 2009) recommended that the whole TPV system has to be considered simultaneously in determining its overall conversion efficiency. Badescu (2005) reported that experimental results showed that the overall TPV system efficiency is typically between 11 and 26% as far as broad-band (i.e.…”
Section: Energy-conversion Aspects Of Tpv Power Generation Systemsmentioning
confidence: 99%
“…Second, despite the fact that a number of proposed designs for quasi-monochromatic emitters have been developed, many of the issues concerning their performance at high temperatures have still not been resolved [9[. Finally, very large emitter-to-absorber area ratios require the use of 3D-geometry emitters with a very large aspect ratio [10,11], which introduces problems with the TPV optical cavity design and the integration of PV cell arrays.…”
Section: Introductionmentioning
confidence: 99%